LONG DAYS FOSTER CALLOGENESIS IN SPINACH AND LETTUCE CULTIVARS - `M. Usman; S. Noureen; B. Fatima; Q. Zaman (Journal of Animal and Plant Sciences, 2014)
Explants of different age were cultured on Murashige and Skoog (MS) medium containing auxins and cytokinins in elite leafy vegetables under different photoperiodic conditions to explore in vitro regeneration. Fifteen days old explants produced more calli in both crops compared with 7 days old explants. Though, dark culture conditions triggered more calli on lower levels of 2,4-D (0.5-2.0 mgL-1) compared with higher levels in Cotyledon and Hypocotyl explants, however, calli growth was greater under long days in both crops. Similar better calli growth response was observed on BAP and Kinetin media in leaf disc explants in Lettuce under long days. These studies suggest that light stimulus may boost the endogenous hormonal production and crosstalk of endo and exogenous hormones trigger early calli growth and proliferation. Further studies are implied to analyze the endogenous hormonal regulation in response to photoperiodic changes in leafy vegetables. These studies could be further useful for expressing important biomolecules in the edible leafy vegetables and for exploring somaclonal variation.
Keywords: Photomorphogenesis; light; dark; callus; leafy vegetables